Affordable housing vis a vis affordable financing: does it matter? - Redzuan, Nur Harena; Kassim, Salina (2015)
Home is an important dwelling and basic necessities to everybody. However, there are a number of the home buyers are not afford to own the house due to a lower income level to meet the risen house price in the market. Thus, this study addresses the problem of the gap in affordable housing in Malaysia and the efforts being made to address the gap. The study highlights the issues of challenges of affordable housing and discusses the financing facilities of affordable houses provided by the Malaysia government. This conceptual paper attempts to illustrate the financing facilitates based on an amortization table from different schemes offered to home buyers. The study would recommend the resolution of financing an affordable house through compulsory savings approach to generate dedicated housing funding. The Housing Provident Fund (HPF) program would promote the affordable financing house by self-funded finance systems that operate through compulsory contributions from the residents. The HPF would match the objectives of affordable housing that housing with a social purpose to support those who would not able to afford the financing.